2011
DOI: 10.1074/jbc.m110.199547
|View full text |Cite
|
Sign up to set email alerts
|

IL-17-induced NF-κB Activation via CIKS/Act1

Abstract: Interleukin-17 (IL-17) is essential in host defense against extracellular bacteria and fungi, especially at mucosal sites, but it also contributes significantly to inflammatory and autoimmune disease pathologies. Binding of IL-17 to its receptor leads to recruitment of adaptor protein CIKS/Act1 via heterotypic association of their respective SEFIR domains and activation of transcription factor NF-B; it is not known whether CIKS and/or NF-B are required for all gene induction events. Here we report that CIKS is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(69 citation statements)
references
References 48 publications
3
66
0
Order By: Relevance
“…MCPIP1 was originally discovered as a target of MCP-1 and is upregulated by many inflammatory stimuli (Dhamija et al, 2013; Sonder et al, 2011). IL-17 regulates Zc3h12a through Act1-mediated activation of NF-κB and IKKγ as well as through mRNA stabilization (Somma et al, 2015; Sonder et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MCPIP1 was originally discovered as a target of MCP-1 and is upregulated by many inflammatory stimuli (Dhamija et al, 2013; Sonder et al, 2011). IL-17 regulates Zc3h12a through Act1-mediated activation of NF-κB and IKKγ as well as through mRNA stabilization (Somma et al, 2015; Sonder et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…MCPIP1 was originally discovered as a target of MCP-1 and is upregulated by many inflammatory stimuli (Dhamija et al, 2013; Sonder et al, 2011). IL-17 regulates Zc3h12a through Act1-mediated activation of NF-κB and IKKγ as well as through mRNA stabilization (Somma et al, 2015; Sonder et al, 2011). MCPIP1 belongs to a family of CCCH zinc finger proteins that exhibit RNase activity against inflammatory and viral mRNA transcripts (Uehata and Akira, 2013; Xu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A mimicking decoy peptide of Act1 CC' loop inhibited IL-17 induced inflammatory responses [158]. Though the SEFIR domain is important for IL-17A signaling transduction and inflammatory gene production, other studies also found that, beside to SEFIR domain, the C-terminal region and "TIR-like loop" (TILL) motif of IL-17RA, the cytoplasmic tail region of IL-17RC and the N-terminal domain of Act1, were also critical for IL-17A-mediated signaling [98,170,208,248].…”
Section: Positive Regulatormentioning
confidence: 96%
“…Correspondingly, Tnip1 -deficient mice develop cutaneous inflammation with psoriasiform characteristics, linking findings in this mouse model to the enhanced susceptibility to psoriasis of individuals with TNIP1 SNPs [96]. Finally, the endoribonuclease MCPIP1 (also known as Regnase-1, encoded by ZC3H12A ) limits IL-17 signaling through the degradation of IL-17-driven genes, including Il6 , Nfkbiz and Il17ra and Il17rc [9799]. To date, 11 non-synonymous SNPs have been described for the ZC3H12A gene, but so far none are associated with human disease [100].…”
Section: Il-17 Cytokine Signaling and Regulationmentioning
confidence: 99%